In vitro construction of yeast tRNAAsp variants: nucleotide substitutions and additions in T-stem and T-loop. - Carbon, P (Nucleic Acids Res, 1987)
A procedure for the construction of 3'-end labelled yeast tRNAAsp harboring substitutions or additions of any desired nucleotide in T-stem and T-loop (position 57 to 61) has been developed. This was done by in vitro enzymatic manipulations of the yeast tRNAAsp involving specific hydrolysis with RNases, phosphorylation and dephosphorylation with T4 polynucleotide kinase and ligation with T4 RNA ligase. Using this procedure we have replaced conserved or semi-conserved nucleotides located in position 57 to 61 of yeast tRNAAsp. We have also constructed different yeast tRNAAsp with eight bases instead of seven in T-loop. Further use of these tRNAAsp variants will be discussed with the help of the crystallographic three-dimensional structure. IMAGES: